TOAST classification and risk factors of ischemic stroke in Lebanon. (13th December 2019) - Malek, Elia G.; Elbejjani, Martine; Abbas, Rawad; Abed Al Ahad, Mary; Isma'eel, Hussein; Makki, Achraf
Abstract : Objectives: Ischemic stroke is a common cause of morbidity and mortality especially in the increasingly older population. The variability in ischemic stroke subtypes and its risk factors across different populations suggest that more effort is needed to describe the stroke characteristics in order to develop a more tailored management for each population. We aim to describe the demographic characteristics, risk factors, and subtype distribution of subjects with ischemic stroke in the Lebanese population. Materials and methods: We conducted a cross‐sectional study based on chart review on patients with ischemic stroke/transient ischemic attack at the American University of Beirut Medical center between 2015 and 2017. Results: A total of 284 cases were included with a mean age of 72 years, and 58% male gender. The most commonly identified risk factors were hypertension (77%), dyslipidemia (62%), and diabetes mellitus (42%), while atrial fibrillation was only found in 27% of cases. The cohort distribution according to TOAST classification was as follows: 15% large artery stroke, 31% cardioembolic stroke, 17% small artery stroke, 10% stroke of other determined causes, and 27% stroke of unknown cause. Conclusion: This is the first study to address ischemic stroke characteristics in Lebanon.